Long‐Term Prognostic Implications of Cerebral Microbleeds in Chinese Patients With Ischemic Stroke. Issue 12 (7th December 2017) - Lau, Kui Kai; Wong, Yuen Kwun; Teo, Kay Cheong; Chang, Richard S. K.; Tse, Man Yu; Hoi, Chu Peng; Chan, Chung Yan; Chan, Oi Ling; Cheung, Ryan Hoi Kit; Wong, Edmund Ka Ming; Kwan, Joseph Shiu Kwong; Hui, Edward S.; et al.
Abstract : Background: This study was performed to determine the clinical correlates and long‐term prognostic implications of microbleed burden and location in Chinese patients with ischemic stroke. Methods and Results: We recruited 1003 predominantly Chinese patients with ischemic stroke who received magnetic resonance imaging at the University of Hong Kong. We determined the clinical correlates of microbleeds and the long‐term risks (3126 patient‐years of follow‐up) of recurrent ischemic stroke and intracerebral hemorrhage (ICH) by microbleed burden (0 versus 1, 2–4, and ≥5) and location, adjusting for age, sex, and vascular risk factors and stratified by antithrombotic use. Microbleeds were present in 450 of 1003 of the study population (119/450 had ≥5, 187/450 had mixed location). Having ≥5 microbleeds was independently associated with prior antiplatelet and anticoagulant use, whereas microbleeds of mixed location were independently associated with hypertension and prior anticoagulant use (all P <0.05). Microbleed burden was associated with an increased risk of ICH (microbleed burden versus no microbleeds: 1 microbleed: multivariate hazard ratio: 0.59 [95% confidence interval, 0.07–5.05]; 2–4 microbleeds: multivariate hazard ratio: 2.14 [95% confidence interval, 0.50–9.12]; ≥5 microbleeds: multivariate hazard ratio: 9.51 [95% confidence interval, 3.25–27.81]; P trend <0.0001), but the relationship of microbleed burden and risk of recurrent ischemic stroke was not significant ( P trend =0.054). Similar findings were noted in the 862 of 1003 patients treated with antiplatelet agents only (ICH: P trend <0.0001; ischemic stroke P trend =0.096). Multivariate analysis revealed that, independent of vascular risk factors, antithrombotic use, and other neuroimaging markers of small vessel disease, having ≥5 microbleeds (multivariate hazard ratio: 6.08 [95% confidence interval, 1.11–33.21]; P =0.037) was identified as an independent predictor of subsequent ICH, but neither microbleed burden nor location was predictive of recurrent ischemic stroke risk. Conclusions: In Chinese patients with ischemic stroke, a high burden of cerebral microbleeds was significantly associated with an increased risk of ICH; however, neither microbleed location nor burden was associated with recurrent ischemic stroke risk.